Hair straighteners: an approach based on science and consumer profile (Brazilian Journal of Pharmaceutical Sciences, 2018)
Technological progress has allowed women to change their natural hair configuration according to their will. This type of treatment is very popular around the world, even involving the use of prohibited chemicals, such as formaldehyde. Studies of hair characterization, straighteners and toxic evaluation are available in the literature, although few studies have evaluated the consumer profile or the current legislation of Brazil and the European Union (EU) and its influence on the consumption of hair straighteners. Previous studies from our research group have shown that hair care is essential for the quality of life and well-being of women. Within this context, the present study aimed to evaluate the profile of Brazilian hair straightener consumers, as well as the legislation of Brazil and the EU and its influence on the use of these products. The consumer profile was evaluated by applying questionnaires and the legislation was examined using documental and bibliographic exploratory research. The results provided a full understanding of the current legislation of Brazil and its similarities to EU legislation. It was observed that over 50% of Brazilians currently use or have previously used hair straightener products, even persons who do not have curly hair, suggesting that straight hair is more attractive for today’s society. Although the study participants consider the current legislation to be important, over 40% do not know the active ingredients present in the hair straightener they use. Finally, the legislation is not considered in terms of the daily hair treatment routine, with the esthetic result being more important to the consumer.